Pain modeling and NSAID pharmacology in meat-type goats: development, comparative efficacy, and pharmacokinetics - Weeder, Mikaela Marlene (My University, 2025)
In recent years, there has been a growing trend among consumers of animal products to prioritize the ethical treatment of animals. Most animal products are derived from food-producing animals, including but not limited to cattle, pigs, poultry, sheep, and goats. Ensuring the ethical treatment of food animals includes addressing a range of animal welfare concerns, including pain recognition and pain alleviation. Pain responses in livestock animals are often challenging to interpret and assess objectively due to their complex nature and the inherent stoicism of prey animal species. This stoicism, while adaptive for survival, complicates the recognition and effective treatment of pain in food animal species, making pain management a significant welfare and veterinary challenge. Goats have become increasingly popular in recent years, both as companion animals and for production purposes. However, compared to other livestock species, the timely and accurate recognition and treatment of pain in goats remains limited. Painful events in goats commonly arise from routine husbandry procedures such as disbudding and castration, as well as from health conditions like lameness or mastitis. While these events are challenging, effective pain management is essential for ensuring positive animal welfare and optimizing productivity. Efficient and timely pain management not only ensures the ethical treatment of livestock animals like goats but also helps address growing concerns among consumers of animal products regarding animal welfare. This dissertation presents a comprehensive evaluation of three amphotericin B-induced lameness models to develop a reliable and repeatable transient synovitis model in meat-type goats. A species-specific grimace scoring system for goats is also introduced to support behavioral pain assessment. The analgesic efficacy of firocoxib and meloxicam is assessed following surgical castration in meat-type goats. Additionally, the effectiveness of firocoxib, meloxicam, and transdermal flunixin, each administered at three different dosages, is evaluated after lameness induction with amphotericin B, using both behavioral assessments and pain-specific biomarkers. Finally, the pharmacokinetic profiles of firocoxib, meloxicam, and transdermal flunixin at varying dosages are reported using descriptive statistical analyses. The results indicate that an amphotericin B lameness model, using a dose of 5 mg/0.25 mL, is a reliable and repeatable method for inducing transient synovitis in meat-type goats for research purposes. Pain assessment tools, including Visual Lameness Scoring (VLS), Visual Analogue Scoring (VAS), and Grimace Scoring, consistently indicated that lameness is a painful condition in goats. Additionally, the Grimace Scoring System developed specifically for evaluating facial expressions in goats during this study proved to be a successful tool for assessing pain-related grimacing behavior. Our results suggest that pain experienced by male goats during surgical castration may be effectively alleviated through the administration of oral meloxicam. The current study provides evidence that surgical castration is a painful husbandry procedure for goats, as demonstrated by multiple pain assessment methods, including kinetic gait analysis, plasma cortisol levels, and Visual Analogue Scoring (VAS). Kinetic gait analysis revealed altered weight distribution, with reduced weight-bearing in the rear limbs compared to the front limbs following castration. Plasma cortisol concentrations peaked immediately after castration but decreased following analgesic intervention. Additionally, VAS scores were consistently higher at 24, 48, and 72 hours post-castration in goats treated with firocoxib compared to those treated with meloxicam or control goats, suggesting meloxicam may offer more effective pain relief. In goats with experimentally induced lameness, analgesic interventions with transdermal flunixin at 3.3 mg/kg and 5.0 mg/kg were effective in reducing pain. Among treatments, the Mechanical Nociception Threshold (MNT) difference between lame and sound limbs was lowest in the high-dose transdermal flunixin group (5.0 mg/kg), indicating effective analgesia. Kinetic gait parameters, including stance time, stride length, peak force, and contact force, showed the smallest differences between lame and sound limb comparisons in the low-and high-dose transdermal flunixin groups (3.3mg/kg and 5.0mg/kg). Visual Lameness Scores (VLS) were reported to be lowest in the low-dose flunixin group on average (3.3 mg/kg), while Visual Analogue Scores (VAS) were lowest in the high-dose group on average (5.0 mg/kg). Descriptive pharmacokinetic data were collected for firocoxib, meloxicam, and transdermal flunixin at three dosage levels for each drug. To conclude, these results indicate that pain-associated outcome measures previously used in livestock species such as cattle are also effective in assessing pain in goats. There is a clear animal welfare benefit for meat goats that receive analgesia prior to or during painful procedures, such as surgical castration or treatment for lameness. Further research is warranted to investigate species-specific pain indicators relevant to goats, and to optimize analgesic strategies for managing pain during procedures like castration or in cases of lameness. Such studies will help provide more effective pain control options for meat-type goats.
Keywords: Goat; Pain; Analgesia; Lameness; Castration; Pharmacokinetics